Analisis Efektivitas Pemutihan Sanksi Administrasi Pajak Kendaraan Bermotor Dalam Upaya Meningkatkan Pajak Daerah Tahun 2018-2020 ( Studi Kasus Di Kantor Pusat Pengelola Pendapatan Daerah Wilayah Kota Bekasi ) - Eva Fauziah; Mainita Hidayati (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
The existing perpetual arrears of vehicle taxes phenomenon pushes the government to provide relief for the people through a motor vehicle tax penalty relief program. Based on this background, this paper aims to study the effectiveness of the motor vehicle tax administration penalty relief to increase regional income at the regional revenue management agency in Bekasi city. This research employs a descriptive method with a qualitative approach, using data collection techniques, namely observation, interviews, and documentation. According to Dunn in Hertati & Martadani (2019), the focus of the said program consist oh 5 ( Five ) indicators, namely efficiency, coverage, care/equality, responsiveness, and accuracy. The results of this study show that 1) the efficiency of the relief program implementation has been effective because it can increase tax awareness in playing vehicle taxes 2) the scope ability to relief penalty has been effective because it can reduce the burden on the taxpayers 3) Equalization/equality in the penalty relief has been effective all the taxpayers who have motorized vehicle can participate in this program 4) the responsiveness of the relief has not been effective yet because many taxpayers are unaware of this program 5) the accuracy of the relief has been effective because the government provides relief from tax penalties during the covid-19 pandemic, amidst the economic declination. The effectiveness of the tax administration penalty relief in the city of Bekasi has been effective. However, in terms of its implementation, many taxpayers are still unaware of this program.